2011
DOI: 10.1111/j.1582-4934.2011.01259.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral transplantation of foetal neural stem cells improves brain dysfunction induced by intracerebral haemorrhage stroke in mice

Abstract: Intracerebral haemorrhage (ICH) can lead to secondary insults and severe neurological deficits. Transplantation of neural stem cells (NSCs) was suggested as an alternative to improve ICH-induced neurological dysfunction. The present study aimed at investigating the therapeutic role and long-term survival of foetal NSCs and potential role of foetal NSCs-produced factors in ICH. Our results demonstrated that foetal NSCs could differentiate into neural axons and dendrites and astrocytes in both in vitro and in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…While there have been previous reports using NSC transplantation in ICH, most of these studies transplanted cells at later time points to study their effects on functional recovery. 5,6,8 In our study, we focused on the effects of transplants during the acute stage to examine the ability of these cells to survive during this critical period, as well as the potential for neuroprotection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there have been previous reports using NSC transplantation in ICH, most of these studies transplanted cells at later time points to study their effects on functional recovery. 5,6,8 In our study, we focused on the effects of transplants during the acute stage to examine the ability of these cells to survive during this critical period, as well as the potential for neuroprotection.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown the neuroprotection of intraparenchymal cell transplants that can ameliorate primary and secondary injury in animals with ICH, as well as enhance functional recovery. [5][6][7][8][9][10][11][12] At the site of neuroprotection, the transplantation should be performed at the acute stage of ICH, because the irreversible brain damage extends as time goes by. However, the hostile host environment during the acute stage of ICH limits the efficacy of this strategy as more than 85% of transplanted cells are no longer present 8 weeks after transplant.…”
Section: Introductionmentioning
confidence: 99%
“…Many stem cell administration routes have been tested, but it remains unclear which is the best option. Findings in ICH model support that cervical vein delivery is inefficient [133] , whereas good outcomes were already observed following stem cell delivery in brain parenchyma [66,111,[113][114][115][116]121,126,[134][135][136][137] , lateral ventricle [120,133] , tail vein [117,119,122,[124][125][126]138,139] , and carotid artery [133,140,141] . However, each one of these alternatives has drawbacks.…”
Section: Preclinical Studies: An Heterogeneous Approach For An Heteromentioning
confidence: 70%
“…; 1 × 10 6 1000; 2000 TV Vaquero et al [136] Col Ⅳ hBMSC [119] Col Ⅶ BMSC 1 h 1 × 10 6 1000 TV Wang et al [137] Col Ⅶ NSC 72 h 1 × 10 6 500 (TV); 2 (BP) TV; BP Yang et al [121] Col Ⅰ BMSC (overexpressing GDNF) 72 h 5 × 10 5 20 BP Yang et al [117] ABI hUCSC 24 h; 72 h; 7 d 3 × 10 6 2000 TV Yang et al [159] Col Ⅶ hASC 24 h 1 × 10 6 200 FV Zhang et al [133] Col Ⅶ …”
mentioning
confidence: 99%
“…5,6,8,38 The present SOD1 enhances stem cell therapy in mouse ICH T Wakai et al study shows that transplantation of SOD1 Tg NSCs in ICH brains reduced their atrophy and death. Moreover, an improvement in the outcome of behavioral tests was observed in these animals, indicating that stem cells facilitate neuroprotection after being grafted to ICH brains.…”
Section: Discussionmentioning
confidence: 86%